The Design and Implementation of Formative Assessment in British Literature - Liu, Liping (Journal of Theory and Practice in Linguistics, 2024)
Formative assessment, also known as process-oriented assessment, emphasizes timely feedback to students throughout the learning process. Unlike summative assessment, which primarily evaluates student performance based on final exams and often overlooks the importance of continuous learning efforts, formative assessment provides ongoing support and evaluation. Extensive research across various educational levels and disciplines in China has demonstrated the positive impact of formative assessment on student learning. However, there is a notable gap in the literature regarding its application in British Literature courses. This paper presents a case study of formative assessment design and implementation for a British Literature course at Lingnan Normal University's School of Foreign Studies. The study was conducted among English-major juniors during the second semester of the 2018-2019 academic year. A questionnaire was administered to assess the impact of this assessment method on student learning. The results indicate that formative assessment significantly benefited students in multiple aspects.